ArsV and ArsW provide synergistic resistance to the antibiotic methylarsenite. (21st October 2021) - Chen, Jian; Zhang, Jun; Wu, Yi‐Fei; Zhao, Fang‐Jie; Rosen, Barry P.
Summary: Toxic organoarsenicals enter the environment from biogenic and anthropogenic activities such as microbial methylation of inorganic arsenic and pentavalent herbicides such as monosodium methylarsenate (MSMA or MAs(V)). Trivalent MAs(III) is considerably more toxic than arsenite or arsenate. Microbes have evolved mechanisms to detoxify organoarsenicals. We previously identified ArsV, a flavin‐linked monooxygenase and demonstrated that it confers resistance to methylarsenite by oxidation to methylarsenate. The arsV gene is usually in an arsenic resistance ( ars ) operon controlled by an ArsR repressor and adjacent to a methylarsenite efflux gene, either arsK or a gene for a putative transporter. Here we show that Paracoccus sp. SY oxidizes methylarsenite. It has an ars operon with three genes, arsR, arsV and a transport gene termed arsW . Heterologous expression of arsV in Escherichia coli conferred resistance to MAs(III), while arsW did not. Co‐expression of arsV and arsW increased resistance compared with either alone. The cells oxidized methylarsenite and accumulated less methylarsenate. Everted membrane vesicles from E. coli cells expressing arsW ‐accumulated methylarsenate. We propose that ArsV is a monooxygenase that oxidizes methylarsenite to methylarsenate, which is extruded by ArsW, one of only a few known pentavalent organoarsenical efflux permeases, a novel pathway of organoarsenical resistance.